Financial Transmission Rights Analysis, Experiences and Prospects - Rosellón, Juan; Kristiansen, Tarjei (Lecture Notes in Energy, 2013)
Whilst financial rights have appeared as a successful ingredient in North-American power markets, they have their shortcomings both theoretically and in practice. Financial Transmission Rights: Analysis, Experiences and Prospects present a systematic and comprehensive overview of financial transmission rights (FTRS). Following a general introduction to FTRs, including chapters to explain transmission pricing and the general properties of FTRS, experts in the field provide discussions on wide scope of topics. These include: ·Varying perspectives on FTRS: from electrical engineers to economists, ·Different mathematical formulations of FTRS ·Financial Hedging using FTRS, and ·Alternative solutions to FTRs The detail, expertise and range of content makes Financial Transmission Rights: Analysis, Experiences and Prospect  an essential resource for electricity market specialists both at academic and professional levels. "This is THE BOOK we were all expecting to address all key 'Financial Transmission Rights' issues. It is comprehensive and reader friendly. You can pick at will in its menu: more or less theory, a bit of maths or none, empirical review of real cases or numerical simulations of many feasible options. Big names rally there to delight you like: Hogan , Oren, Perez-Arriaga, Smeers, Hobbs and... Rosellón. More than a must read: a light house, a map and a survival kit."  Jean - Michel Glachant, Director Florence School, Holder Loyola de Palacio Chair, Chief-editor Economics of Energy & Environmental Policy. "In the last two decades, economists have developed a better understanding of the impact of financial rights on risk management, market power and network expansion in electricity markets, while power systems have experimented with such rights. Striking a good balance between academics and practitioners, always at the frontier of the field, written by the best experts, this volume is essential reading for all those- power systems' managers and users, regulators, students and researchers- who want to understand the new electricity environment and predict its evolution." Jean Tirole, Toulouse School of Economics and Institute for Industrial Economics (IDEI) Further comments inside.